Search for top squark pair production in the dielectron channel - Abachi, S; Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alvarez, G; Alves, G; Amidi, E; et al. (1998)
This report describes the first search for top squark pair production in the channel t̃1t̄̃1→bb̄χ 1̃+χ1̃-→ee+jets+ET using 74.9±8.9 pb-1 of data collected using the DØ detector. A 95% confidence level upper limit on σ· B is presented. The limit is above the theoretical expectation for σ· B for this process, but does show the sensitivity of the current DØ data set to a particular topology for new physics.